‘Did he get to second base?’ –baseball metaphor as a means of describing the degree of physical intimacy in the fifty shades trilogy - Kurowska, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The main aim of this article is to demonstrate the mechanism of the SEX IS BASEBALL metaphor, and to focus on its motivation, as well as on its possibly degrading effect on modern society. The concept of conceptual metaphor proposed by Lakoff and Johnson (1980) and further discussed by other scholars constitutes one of the most expedient devices that can be applied in this kind of research.

Głównym celem artykułu jest przedstawienie mechanizmu metafory SEKS TO BASEBALL oraz uwypuklenie jej możliwie deprecjonującego wpływu na współczesne społeczeństwo. Koncepcja metafory pojęciowej zaproponowana przez Lakoffa i Johnsona (1980) i dalej rozwijana przez innych badaczy wydaje się być jednym z najpraktyczniejszych narzędzi używanych w tego typu badaniach.
Keywords: baseball; sex; metaphor; base; seks; metafora; baza